High-performance supercapacitor based on V2O5/carbon nanotubes-super activated carbon ternary composite. Issue 10 (1st August 2016) - Wang, Qingyong; Zou, Yongjin; Xiang, Cuili; Chu, Hailiang; Zhang, Huanzhi; Xu, Fen; Sun, Lixian; Tang, Chengying
Abstract: A ternary composite of V2 O5 /carbon nanotubes/super activated carbon (V2 O5 /CNTs–SAC) was prepared by a simple hydrothermal method and used as a supercapacitor electrode material. The electrochemical performance of the electrode was analyzed using cyclic voltammetry, galvanostatic charge/discharge measurements, and electrochemical impedance spectroscopy, which were performed in 2 M NaNO3 as the electrolyte. The V2 O5 /CNTs–SAC nanocomposite exhibited a specific capacitance as high as 357.5 F g −1 at a current density of 10 A g −1, which is much higher than that of either bare V2 O5 nanosheets or a V2 O5 /CNTs composite. Furthermore, the capacitance increased to 128.7% of the initial value after 200 cycles, with 99.5% of the maximum value being retained after 1000 cycles. These results demonstrated that the V2 O5 /CNTs–SAC ternary composite is suitable for use as an electrode material for supercapacitors.